Immunological Features of Pediatric Interstitial Pneumonia Due to Mycoplasma pneumoniae - Xu, Xuefeng; Sheng, Yuanjian; Yang, Li; Zhou, Haichun; Tang, Lanfang; Du, Lizhong (Frontiers in Pediatrics, 2021)
Background: Inflammatory response, oxidative stress, and immunologic mechanism are involved in the pathogenesis of M. pneumoniae pneumonia (MPP). However, the role of the immune system of pediatric interstitial pneumonia due to M. pneumoniae infections remains poorly understood. The aim of this study was to analyze the immunologic features of pediatric interstitial pneumonia due to M. pneumoniae. Methods: A retrospective study was conducted on a primary cohort of children with MPP. Propensity score analysis was performed to match interstitial pneumonia and pulmonary consolidation children. Results: The clinical characteristics strongly associated with the development of interstitial pneumonia were boys, age > 5 years, wheezing history, hydrothorax free, lymphocytes (> 3.0 x 109/L), CD19+ (> 0.9 x 109/L), CD3+ (> 2.5 x 109/L), CD4+ (> 1.5 x 109/L), CD8+ (> 0.9 x 109/L), interleukin-6 (IL-6, < 30 pg/ml), IL-10 (< 6 pg/ml), and interferon-γ (IFN-γ, < 15 pg/ml). After propensity score analysis, children with interstitial pneumonia showed significantly higher CD19+, CD3+, and CD4+ T cell counts, and lower serum IL-6, IL-10, and IFN-γ levels. The final regression model showed that only CD4+ T cells (> 1.5 x 109/L, OR = 2.473), IFN-γ (< 15 pg/ml, OR = 2.250), and hydrothorax free (OR = 14.454) were correlated with the development of interstitial pneumonia among children with MPP. Conclusions: The M. pneumoniae-induced interstitial pneumonia showed increased CD4+ T cells and lower serum IFN-γ level. Specific immunologic profiles could be involved in the development of pediatric interstitial pneumonia due to M. pneumoniae infections.